Linking DNA damage and senescence to gestation period and lifespan in placental mammals - Singh, Vijay Pratap; Singh, Pushpendra (Frontiers in Cell and Developmental Biology, 2024)
The mechanism that synchronizes the timing of parturition remains a mystery. Each mammalian species has a specific duration of gestation, which is determined by integrated interactions among mother, placenta, and fetus. Senescence, primarily driven by DNA damage, is one of the critical factors influencing both parturition and lifespan. In this study, we investigated senescence as a physiological process during pregnancy and observed a gradual physiological increase in senescence in the mother’s decidua and placental cells with gestation. This increase in senescence was associated with gradual and physiological increase in DNA damage during gestation. An analysis of AnAge data, revealed a positive correlation between the gestation period and maximum lifespan across 740 mammalian species. This finding supports the hypothesis that rates of DNA damage and senescence may impact both gestation period and lifespan. We suggest that the relationship between gestation period and lifespan in mammals is mediated by species-specific rates of DNA damage and senescence, and their causal role should be explored further.